Management of the business system of the enterprise - O. Grosheleva; M. Ivanova; O. Usatenko (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет)
The ways to improve enterprise communication policy management to strength its market position are proposed. It’s shown that in conditions of saturation of the markets as well as oversaturation of information space the choice of effective tools of communication policy will improve competitive position. The analysis of modern publications allowed to determine the absence of both common approach to understanding of content and structure of optimal communication policy and methods of its evaluation. The lack of direct correlation between total expenses of enterprise spent to communication policy and amount of sales is proved. The prominent role of optimizing the budgeting of communication process is substantiated. The final goal of implementation of enterprise communication policy, operating in B2B segment, is proposed. The usage of economic method to evaluate the budget of promoting as an optimal method for industrial enterprise is substantiated. The model based on regression method implementation is developed. It confirms the effect of the law of marginal utility costs for communication with the external environment. An algorithm for determining the optimal share of sales costs in revenue is proposed. An algorithm to rationalize the cost structure directed to the tools of communication policy within the calculated optimal budget using a multiple correlation coefficient, partial correlation coefficients, regression analysis tools, optimization method is recommended. An optimization model has been built, which allows to determine the share of expenditures for certain communication activities in the overall budget structure. The approach to calculation of influence of change of expenses structure on measures of communication policy on dynamics of volumes of company’s sales is shown.